BRIDGING THE GAP: ASSESSING VOLUNTEERISM ENGAGEMENT AND INSTITUTIONAL SUPPORT NEEDS AMONG MALAYSIAN TVET STUDENTS - Nur Hidayah Binti Zainul; Mohd Fazlon Abdul Rahim (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study examines volunteerism engagement among TVET students at Seberang Perai Polytechnic, Malaysia, focusing on participation patterns, understanding, and institutional support needs. Using quantitative methods, a Likert-scale questionnaire assessed 189 students’ volunteer experiences, comprehension, perceived benefits, and support expectations. Data were analyzed via descriptive and inferential statistics. Key findings reveal 72.3% of students had volunteer experience, with participation frequency ranging from 5+ annual engagements to none. Community service (41.2%) and environmental activities (28.7%) were most common. Students showed strong understanding (M=4.21/5), with 89.1% recognizing societal benefits and 92.4% valuing personal skill development. However, 68.5% cited time constraints as the main barrier, while 54.7% reported insufficient institutional support. Significantly, 83.9% advocated for curriculum integration and 76.2% requested formal recognition mechanisms.Despite high awareness and participation, structural challenges limit optimal engagement. The study recommends: (1) implementing credit-bearing volunteer modules, (2) establishing reward systems, and (3) conducting targeted awareness campaigns.These evidence-based strategies aim to strengthen community engagement while supporting Malaysia’s education transformation goals in TVET institutions.